Multifaceted Islam: Malaysia - Ju. V. Roknifard (Международная аналитика, 2021)
This paper analyzes the Islam’s impact on the Malaysian politics. Islam as an instrument of Malaysia’s foreign policy has been used by the political elite of the state for decades. Observers note the Islamization of the country’s foreign policy, especially during the premiership of Najib Razak (2008– 2018). However, the trend towards Islamization can be traced back to the moment Malaysia gained independence from Great Britain in 1957 and especially during the premiership of Mahathir Mohamad (1981–2003). The formation of such a foreign policy of Malaysia took place against the background of the Islamization of the political and social environment within the country, which, in turn, was the result of an internal political struggle. Thus, the projection of Malaysia’s identity into the outside world and the foreign policy corresponding to this identity was often motivated by the need to retain or attract the support of the malay-muslim majority in the domestic political arena. Since many of the issues raised in the article relate to identity both at the national and global level, a constructivist paradigm is used to conceptualize Malaysia’s foreign policy with a special emphasis on the identity of states. Particularly important in this process is the formation of domestic and foreign policy discourse. Malaysia’s Islamic identity is viewed externally in three dimensions: the Sunni state, the activist state in the Islamic world and the standard of moderate Islam. Consideration of these dimensions reveals quite obvious contradictions between them, as well as between rhetoric and real politics.